The Mediating Role of Brand Trust in Brand Loyalty on Indonesia’s Local Women’s Fashion - Belinda Aprilia; Fredianaika Istanti (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Indonesia’s fashion industry is growing rapidly, as indicated by increasing consumer spending on fashion products. High fashion imports raise concerns about consumer perceptions of local versus foreign brands, underscoring the need to examine loyalty drivers among female consumers of local fashion in Semarang amid rising income and purchasing power. This study assesses the impact of social media marketing, brand awareness, and brand image on brand loyalty with brand trust acts as mediator. A quantitative explanatory study with 180 non-probability purposively sampled respondents, following Hair’s sample size guideline and employing a five-point Likert scale, was analyzed the measurement and structural models with PLS-SEM. The findings indicate that social media marketing, brand awareness, and brand image significantly impact brand trust. Social media marketing and brand image influence brand loyalty, with social media marketing emerging as the most dominant predictor. In contrast, brand awareness does not affect directly on brand loyalty. Furthermore, brand trust mediates the influence of social media marketing, brand awareness, and brand image on brand loyalty. Local fashion should strengthen awareness to build trust and sustain loyalty.